Effects of purified eicosapentaenoic and docosahexaenoic acids in nonalcoholic fatty liver disease: Results from the WELCOME* study. Issue 4 (25th August 2014) - Scorletti, Eleonora; Bhatia, Lokpal; McCormick, Keith G.; Clough, Geraldine F.; Nash, Kathryn; Hodson, Leanne; Moyses, Helen E.; Calder, Philip C.; Byrne, Christopher D.; on behalf of the WELCOME Study Investigators; Sheron, Nick; Wright, Mark; et al.
<x xml:space="preserve">Abstract</x> There is no licensed treatment for nonalcoholic fatty liver disease (NAFLD), a condition that increases risk of chronic liver disease, type 2 diabetes, and cardiovascular disease. We tested whether 15‐18 months of treatment with docosahexaenoic acid (DHA) plus eicosapentaenoic acid (EPA; Omacor/Lovaza, 4 g/day) decreased liver fat and improved two histologically validated liver fibrosis biomarker scores (primary outcomes). Patients with NAFLD were randomized in a double‐blind, placebo‐controlled trial (DHA+EPA, n = 51; placebo, n = 52). We quantified liver fat percentage by magnetic resonance spectroscopy in three liver zones. We measured liver fibrosis using two validated scores. We tested adherence to the intervention (Omacor group) and contamination (with DHA and EPA; placebo group) by measuring erythrocyte percentage DHA and EPA enrichment (gas chromatography). We undertook multivariable linear regression to test effects of (1) DHA+EPA treatment (intention‐to‐treat analyses) and (2) erythrocyte DHA and EPA enrichment (secondary analysis). Median (interquartile range) baseline and end‐of‐study liver fat percentage were 21.7 (19.3) and 19.7 (18.0) (placebo) and 23.0 (36.2) and 16.3 (22.0) (DHA+EPA). In the fully adjusted regression model, there was a trend toward improvement in liver fat percentage with DHA+EPA treatment (β = −3.64; 95% confidence interval [CI]: −8.0, 0.8; P = 0.1), but there was evidence of contamination in the placebo group and variable adherence to the intervention in the Omacor group. Further regression analysis showed that DHA enrichment was independently associated with a decrease in liver fat percentage (for each 1% enrichment: β = −1.70; 95% CI: −2.9, −0.5; P = 0.007). No improvement in fibrosis scores occurred. Conclusion: Erythrocyte DHA enrichment with DHA+EPA treatment is linearly associated with decreased liver fat percentage. Substantial decreases in liver fat percentage can be achieved with high‐percentage erythrocyte DHA enrichment in NAFLD. (Hepatology 2014;60:1211–1221)